Strategi Kelompok Musik Gambang Kromong dalam Menghadapi Perubahan Sosial : Studi Kasus Gambang Kromong Sanggar Margasari - Arini, Arini Afidatul Azkiya; Cahya, Arum Nilam; Alfarisi, Fahri Salman (Sociology Study Program, Faculty of Social Science and Law, Universitas Negeri Jakarta, 2023)
This article explores the traditional Betawi music called Gambang Kromong and its evolving role in contemporary society. The diverse Betawi community possesses unique traditions and lifestyles, including the distinctive Gambang Kromong music. However, in the face of modern music's growing popularity and the passage of time, traditional art forms like Gambang Kromong are increasingly endangered and less appealing to younger generations. To address this issue, governmental and artistic efforts are being made to preserve Betawi arts, including the establishment of the Betawi Cultural Institute. Sanggar Margasari is one of the groups dedicated to safeguarding Gambang Kromong. Gambang Kromong music, a product of cultural fusion, has experienced transformation and social change influenced by commercial factors. This article also delves into the history and the development of Sanggar Margasari's role in preserving Betawi dance. Sanggar Margasari continues to strive towards maintaining Gambang Kromong as an integral part of their cultural heritage and introducing it to the younger generation.